When you're down and troubled: Views on the regulatory power of music. (November 2015) - Shifriss, Roni; Bodner, Ehud; Palgi, Yuval
This study examined people's beliefs about the impact of music on the regulation of a bad mood. Participants ranging from 24 to 86 years of age ( n = 156) were asked whether they tend to listen to music when feeling bad, and if so, what is the mood of the music (i.e., sad or happy) they choose, and whether they believe that music can improve their mood. Participants completed the Trait Meta-Mood Scale, Music in Mood Regulation Inventory, and Brief Symptoms Inventory. Compared to those who do not listen to music when in a bad mood, participants who do reported directing more attention to their emotions and using strategies for mood regulation through music more intensively, and expressed a stronger belief in their ability to influence their mood through music. Compared to those who prefer listening to sad music when in a bad mood, listeners to happy music reported a stronger tendency to repair mood and a stronger belief in their ability to influence their mood through music. The choice of happy music when in a bad mood was more common among older participants. These results are discussed in relation to theories concerning the role of music in mood regulation in late adulthood.